Modelo de gestión administrativa turística aplicado al complejo Bambú Eco-Resort; que posibilita a los servicios del sector de la educación a adquirir bajo su realidad económica una propiedad vacacional en tiempo compartido. - Ramírez Arboleda, Augusto Reinaldo (2015)
The present investigation proposes an administrative and tourist management model for bamboo Eco-Resort complex, which makes it possible for teachers Ecuadorians, purchased a time-share vacation property, in consideration of their economic reality based on the application of theory value and participative leadership.